The Effect of Online Learning on Student Motivation and Learning Outcomes in a Systematic Literature Review: Pengaruh Pembelajaran Daring Terhadap Motivasi Dan Hasil Belajar Siswa Dalam Systematic Literature Review - Nengsih, Melina Rahayu; Hapsari, Yovita Diva; Rahmawati, Sajidda Andani; Sani, Fidela Amelia; Fakhriyah, Fina; Ismaya, Erik Aditia (Edukasi: Journal of Educational Research, 2023)
This study aims to analyze the effect of online learning on students' learning motivation and outcomes at the elementary school level during the COVID-19 pandemic. The research was conducted using the Systematic Literature Review (SLR) method, by identifying, evaluating, and synthesizing relevant scientific articles from 2019 to 2022. Data were collected from Google Scholar databases and analyzed thematically. The findings show that online learning significantly affects students' motivation, with a contribution rate of 64.01%. Factors influencing learning motivation include internal and external factors, the role of parents, and the use of interactive learning media such as Wordwall. Parental support during online learning also positively affects learning outcomes, while infrastructural barriers such as limited communication tools and internet connectivity pose major challenges. This study implies that strengthening parental involvement and improving digital infrastructure are key to optimizing online learning. The research provides an original contribution by systematically linking parental parenting styles to learning motivation and outcomes in the online learning context, a topic that has been less explored in previous studies.